2022
DOI: 10.5539/ies.v15n1p76
|View full text |Cite
|
Sign up to set email alerts
|

Framework of Artificial Intelligence Learning Platform for Education

Abstract: Nowadays, Information Technology is an integrated as a part of our life activities. It does not affect only teaching and learning methods at all levels, but also the teaching styles of each teacher with suitable for the digital age. Therefore, the standardized platform should create for all teachers to effectively serve the future education policy. This research aims to synthesize and develop a framework of an artificial intelligence learning platform for education and estimate the framework’s suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…Consequently, the incorporation of AI into medical education on a broader national or international scale is limited, and the adoption of frameworks, certification programs, interdisciplinary collaborations, modules, and formal lectures seems still to be at an early stage [18, 4446].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the incorporation of AI into medical education on a broader national or international scale is limited, and the adoption of frameworks, certification programs, interdisciplinary collaborations, modules, and formal lectures seems still to be at an early stage [18, 4446].…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of AI knowledge and education among medical and dentistry students is not a novel phenomenon. Depending on the study and item design, self-reported AI knowledge in the literature ranges from 2.8% of Consequently, the incorporation of AI into medical education on a broader national or international scale is limited, and the adoption of frameworks, certification programs, interdisciplinary collaborations, modules, and formal lectures seems still to be at an early stage [18,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…o Ejemplo: La Universidad de California, Berkeley, desarrolló un marco para la evaluación de herramientas de IA en la educación (Thongprasit & Wannapiroon, 2022).…”
Section: Nota: Autores (2024)unclassified
“…Microsoft cuä ng cung cêë p möå t cöng cuå höî trúå giaã i toaá n úã mûá c àöå phûá c taå p haå n chïë [14]. Caá c "platform" höî trúå hoå c têå p thöng minh nhû trong [15].…”
Section: Caá C Hïå Thöë Ng Trñ Tuïå Nhên Taå O ûá Ng Duå Ng Trong Gia...unclassified